2021
DOI: 10.3390/jcm10225309
|View full text |Cite
|
Sign up to set email alerts
|

Is Chronic Kidney Disease Affecting the Postoperative Complications of Vitrectomy for Proliferative Diabetic Retinopathy?

Abstract: Chronic kidney disease (CKD) is a well-known risk factor for postoperative complications in several surgical fields. However, although prevalent among diabetic candidates for vitrectomy, the effect of CKD on vitrectomy outcomes remains unclear. This study aimed at clarifying the relationship between CKD and the occurrence of vitrectomy-related complications in patients with proliferative diabetic retinopathy (PDR). The 6-month incidences of vitreous hemorrhage (VH) and neovascular glaucoma (NVG) following vitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…The incidence of postoperative VH in PDR had been reported to be around 75% in the 1980s ( 1 , 2 ), but with the development of surgical techniques and instruments, it has decreased to 12–40% in recent years. The risk factors of postoperative VH include younger age, later detection of DM, poor diabetic and hypertension control, higher serum creatinine, broader area of active neovascularization, increased extent of membrane peeling, postoperative hypotony, postoperative residual neovascularization membrane, unrelieved vitreous retinal contraction, and insufficient PRP ( 23 , 24 ). In this study, baseline characters, including age, duration of DM, HbA1c, and patient proportion with renal dysfunction, were compared between the two groups, and vitrectomies were all performed by skillful surgeons with more than 15 years of experience to minimize the selective bias and heterogeneity in surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of postoperative VH in PDR had been reported to be around 75% in the 1980s ( 1 , 2 ), but with the development of surgical techniques and instruments, it has decreased to 12–40% in recent years. The risk factors of postoperative VH include younger age, later detection of DM, poor diabetic and hypertension control, higher serum creatinine, broader area of active neovascularization, increased extent of membrane peeling, postoperative hypotony, postoperative residual neovascularization membrane, unrelieved vitreous retinal contraction, and insufficient PRP ( 23 , 24 ). In this study, baseline characters, including age, duration of DM, HbA1c, and patient proportion with renal dysfunction, were compared between the two groups, and vitrectomies were all performed by skillful surgeons with more than 15 years of experience to minimize the selective bias and heterogeneity in surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative VH, which had been reported to happen in 12-40% vitrectomized PDR patients, will hinder monitoring of disease course and require additional application of laser treatment, therefore delaying visual rehabilitation. The risk factors of postoperative VH include younger age, later detection of DM, poor diabetic and hypertension control, higher serum creatinine, broader area of active neovascularization, increased extent of membrane peeling, postoperative hypotony, postoperative residual neovascularization membrane, unrelieved vitreous retinal contraction and insufficient PRP [28,29]. PRP plays a protective role in disease progression and surgical difficulty of PDR [30].…”
Section: Discussionmentioning
confidence: 99%
“…[14] In the early era of 20-gauge vitrectomy, the in uence of continuing anticoagulation or antiplatelet medicine was suggested to be related to POVH [12,35,36]. In recent studies of small-gauge diabetic vitrectomy, most evidence supports that the continued use of anticoagulation or antiplatelet medication in the perivitrectomy period does not increase the chance of POVH [13,14,17,19,32,37]. Consistent with previous reports, we found that the occurrence of POVH was not signi cantly different between patients for whom anticoagulation or antiplatelet medications were continued (0/22) and patients for whom adjustments were made (11/198).…”
Section: Discussionmentioning
confidence: 99%
“…Previous non-ocular surgery data show that patients with end-stage renal failure are prone to developing postoperative bleeding [41]. In contrast, the data on vitrectomy in renal failure patients showed a contrary result: renal failure and hemodialysis, including heparin dialysis, do not appear to have a deteriorative in uence on the outcomes of diabetic vitrectomy [18,37,42,43]. Our results agree with the previous vitrectomy data; the occurrence of POVH was not different either between patients on dialysis (12) and patients not on dialysis (108) or between patients on heparin dialysis (5,7) and patients on non-heparin dialysis.…”
Section: Limitationsmentioning
confidence: 99%